PENGARUH DISIPLIN KERJA DAN GAYA KEPEMIMPINAN KEPALA SEKOLAH MELALUI MOTIVASI KERJA TERHADAP KINERJA GURU SMPN 1 PENAJAM PASER UTARA - Wiyani Ekowati (Program Pascasarjana Universitas Wijaya Putra Surabaya, 2018)
This study aims to determine the influence of work discipline on teacher performance, the influence of leadership style on work motivation, the influence of work discipline on work motivation, the influence of work motivation on teacher performance, the influence style leadership of the principal to the teachersÔÇÖ performance of SMPN 1 Penajam Paser Utara through work motivation and to analyze the influence of work discipline on the teachersÔÇÖ performance of SMPN 1 Penajam Paser Utara through work motivation. This research uses quantitative approach and explanatory research type. The population in this study was all teachers at SMPN 1 Penajam Paser Utara. The sample of this study amounted to 30 teachers. The results of this study indicate that both leadership style and work discipline have a significant effect on teachersÔÇÖ performance of SMPN 1 Penajam Paser Utara. Work discipline and work motivation and leadership style have a significant effect on the teachersÔÇÖ performance of SMPN 1 Penajam Paser Utara. Work discipline has a significant effect on the performance of SMPN 1 Penajam Paser Utara teachers through work motivation.